Reflexivity and Fantasy: Surprising Encounters From Interpretation to Interruption. (November 2016) - Lapping, Claudia
This article sets out two psychoanalytically informed conceptions of fantasy as a resource for reflexivity in research. First is the fantasy as a defensive structure that distorts our perception of reality, and the use of the researcher's affective responses as an interpretive tool. Second is the fantasy as a signifying structure that constitutes the subject's engagement in reality, foregrounding unconscious symbolic associations. These approaches are traced in the construction and analysis of interview data, exploring (a) a trajectory that interprets fantasy as a defense against difficult emotions, (b) the construction of free associations, and (c) symbolic material that disrupts the interpretation of fantasy as defense.